An ESP needs analysis for management students: Indonesian context - Yulia, Henny; Agustiani, Merie (Indonesian Educational Administration and Leadership Journal (IDEAL), 2019)
Need analysis is an essential part for teachers who teach English for specific purposes. Through need analysis, teachers can determine an effective course design which is suitable for learners’ reasons of learning. This study was conducted to find out the needs of Management students, Economic Faculty of Baturaja University, in learning English. In gathering the data, the researchers distributed a questionnaire, adapted from Hutchinson and Waters, to the thirty students who were chosen randomly. From the data, it was obtained that 56.52% of learners’ goal in learning English is for their future job career. Then, 73.21 % of the learners admitted that they were still in beginner level and 43.47% had difficulties in Speaking. They expected that by having English course, they will have better verbal communication that enables them to speak with colleague fluently. Furthermore, it was also found that learners want some varied activities. The result of this study will become a valuable input for lecturer in designing an appropriate teaching material for the learners.